Removal of the influence of plasma volume fluctuations for the athlete biological passport and stability of haematological variables in active women taking oral contraception. Issue 6 (17th January 2022) - Moreillon, Basile; Equey, Tristan; Astolfi, Tiffany; Salamin, Olivier; Faiss, Raphael
Abstract: The haematological module of the athlete biological passport (ABP) monitors longitudinal haematological variations that could be indicative of blood manipulation. This study applied a multi‐parametric model previously validated in elite cyclists to compare inferred and actual PV variations, whereas the potential influence of the oral contraceptive pill (OCP) cycle on the ABP blood biomarkers and plasma volume (PV) in 14 physically active women taking OCPs was also investigated. Blood and serum samples were collected each week for 8 weeks, and the ABP haematological variables were determined according to the World Anti‐Doping Agency guidelines. Transferrin (sTFN), ferritin (FERR), albumin (ALB), calcium (Ca), creatinine (CRE), total protein (TP) and low‐density lipoprotein (LDL) were additionally computed as 'volume‐sensitive' variables in a multivariate analysis to determine individual estimations of PV variations. Actual PV variations were indirectly measured using a validated carbon monoxide rebreathing method. We hypothesised ABP markers to be stable during a standard OCP cycle and estimated PV variations similar to measured PV variations. Measured PV variations were in good agreement with the predictions and allowed to explain an atypical passport finding (ATPF). The ABP biomarkers, Hbmass and PV were stable over 8 weeks. Significant differences occurred only between Week 7 and Week 1, with lower levels of haemoglobin concentration ([Hb]), haematocrit (HCT) and red blood cell count (RBC)(−4.4%, p < 0.01; −5.1%, p < 0.01; −5.2%, p < 0.01) and higher levels of PV at week 7 (+9%, p = 0.05). We thus concluded that estimating PV variations may help interpret individual ABP haematological profiles in women. Abstract : This study investigated the potential influence of the menstrual cycle on the athlete biological passport blood biomarkers and plasma volume in active women taking oral contraceptive pills. A multi‐parametric model previously validated in elite cyclists was applied to compare inferred and actual PV variations. Some significant intra‐individual PV variations were observed, in good agreement with the estimated PV changes; and it can be concluded that estimating PV variations may help interpret individual ABP haematological profiles in women.